Notes sur la dimension immunitaire des enclaves pétrolières - Nicolas Donner (EchoGéo)
This paper considers the ways of establishing oil enclaves in difficult environments and it focuses on procedures that aim to safeguard the extractive activity from external disturbance and/or hostility. First, in addressing the case of enclaves located in extreme environments (hostile to life), we show that the organization of enclaves is an important tool of their immunization: by producing an inclusive and autonomous space, an "architecture of vacuum "(Sloterdijk) allows to free the activity from the conditions and contingencies of the external environment. Secondly, we move to the case of enclaves established in environments that are inhabited and territorialized, where immunization procedures are enriched by defensive (fencing) and intrusive mechanisms (sustainable practices). Finally we discuss the emergence of an ethical paradigm that tangled in strategies that aim to ensure the continuity of extractive activities.